A multi-mechanism model for cutting simulation: A Ginzburg-Landau type phase gradient and numerical implementations. (15th March 2019) - Cheng, C.; Mahnken, R.
Abstract: Based on the concept of generalized stresses we developed a multi-mechanism model for cutting simulations, where the austenite phase fraction is treated as an extra degree of freedom and its first gradient is involved. In this work we show a new aspect on the phase gradient according to Ginzburg-Landau equation, whose derivation is based on the definition of the free energy being a gradient part and a potential part. In a further part of this work we show some numerical aspects for implementation of the bulk model. We formulate the strong and weak formulations of the model and build the finite element matrix using the isoparametric concept for quadrilateral elements. After that we introduce the integration scheme and the local iteration. To this end, the model is implemented as a user-defined element subroutine for explicit (VUEL) and linked to the FE-program ABAQUS for investigating cutting simulations. At the end, the visualisation with ABAQUS/Viewer is introduced, which is not supported for user-defined element.